2015
DOI: 10.1080/19440049.2015.1019939
|View full text |Cite
|
Sign up to set email alerts
|

Colonisation of winter wheat grain byFusariumspp. and mycotoxin content as dependent on a wheat variety, crop rotation, a crop management system and weather conditions

Abstract: Field experiments were conducted during three consecutive growing seasons (2007/08, 2008/09 and 2009/10) with four winter wheat (Triticum aestivum L.) cultivars - 'Bogatka', 'Kris', 'Satyna' and 'Tonacja' - grown on fields with a three-field crop rotation (winter triticale, spring barley, winter wheat) and in a four-field crop rotation experiment (spring wheat, spring cereals, winter rapeseed, winter wheat). After the harvest, kernels were surface disinfected with 2% NaOCl and then analysed for the internal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 82 publications
5
34
0
Order By: Relevance
“…The same statistical conclusion was also reached by a research group from Slovenia, even if the contamination rate with AFLAs, OTA, fumonisins, DON, ZEA, HT-2, and T-2 toxins was higher for the organic cereal products [30]. In addition, different authors [31] declared that crop management system is the weakest factor influencing the internal colonization of winter wheat kernels by Fusarium fungi.…”
Section: Discussionsupporting
confidence: 56%
“…The same statistical conclusion was also reached by a research group from Slovenia, even if the contamination rate with AFLAs, OTA, fumonisins, DON, ZEA, HT-2, and T-2 toxins was higher for the organic cereal products [30]. In addition, different authors [31] declared that crop management system is the weakest factor influencing the internal colonization of winter wheat kernels by Fusarium fungi.…”
Section: Discussionsupporting
confidence: 56%
“…Weather conditions during the postanthesis period have previously been shown to affect the composition of Fusarium communities in winter wheat grain, and rainfall during the flowering stage is a major determinant of grain infection by Fusarium (12,51). Our results illustrate the role of climate on the overall taxonomic diversity of fungi.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, Alternaria, Cladosporium, and Epicoccum are well known for their allergenic properties (7). Although the drivers of wheat phytopathogen infection, such as climatic factors, wheat cultivar, and cropping history, have been intensively studied (12), little is known about the factors that shape the structure of entire fungal communities (e.g., pesticides) (13), and even less is known about fungal diversity in airborne dust generated during wheat harvesting. Thus, currently the homogeneity of the exposure of grain workers to fungal aerosols from one field to another during their work is difficult to estimate.…”
mentioning
confidence: 99%
“…In the present investigation, a significant effect of the humidity duration on mycotoxin production or amount of fungal DNA was not observed. This finding is in general accordance with previous findings that FP and FL are correlated with drier conditions rather than wet conditions (Xu et al ., ; Parikka et al ., ; Czaban et al ., ). However, testing the influence of water activity on FL growth in vitro , Medina & Magan () observed that no growth occurred at a water activity of 0.9 or below and that the optimum was >0.98.…”
Section: Discussionmentioning
confidence: 97%